MENGENALKAN BERITA KONTEMPORER DALAM PEMBELAJARAN BAHASA INDONESIA - Degita Danur Suharsono (Universitas Negeri Surabaya, 2016)
The studies development jurnalitik and digitalisasi mass media indirectly have gave rise to the form of new journalism, named contemporary journalism. Contemporary journalism is a form of journalism the present time without there was a limit. One of the products of journalism contemporary is the news contemporary. News having some kind of contemporary, among others news residents, online news, and the advertorial.In education sector, news is one of text that learned at 2013 curriculum class XII high school. This paper aimed to introduce and develop the form of and types of text news contemporary in learning the Indonesian language. With the contemporary news, learning text news in school is expected to be more varied. Contemporary news also expected to capable of being a innovation learning the indonesian language in the future now. In addition, contemporary news can be realizing one of the programs of 14 kreativ economic program.